Selection of Gate Dielectrics for ZnO Based Thin-Film Transistors - Vaibhav Garg; Navneet Gupta (Institute of Advanced Engineering and Science, 2016)
The bulk of semiconductor technology has been based on silicon till today. But silicon has its own limitations. It is not transparent to visible light and hence it cannot be used in certain applications. ZnO is a material which is transparent to visible light. In this paper, we compare the electrical performance of ZnO Thin film Transistors using different gate insulators. Certain performance indices and material indices were considered as the selection criteria for electrical performance. A methodology known as Ashby’s approach was adopted to find out the best gate insulators and based on this methodology various charts were plotted to compare different properties of competing materials. This work concludes that Y2O3 is the best insulator followed by ZrO2 and HfO2.